2021
DOI: 10.4236/ojrm.2021.102002
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Adipose-Derived Mesenchymal Stem Cells Embedded in Platelet-Rich Fibrin in Diabetic Foot Ulcers

Abstract: Context and Aim: Mesenchymal stem cells (MSCs) and platelet-rich fibrin (PRF) have emerged as ideal candidates for advanced therapies of various therapeutically-challenging diseases; however, their regenerative potential in diabetic foot ulcers (DFU) has not been well determined. In this study, we reviewed our clinical experience in mitigating chronic ulcer complications of diabetic foot through a conventional treatment of autologous adipose-derived MSCs embedded in PRF with pure PRF injections. Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Khalil et al reported that patients receiving AMSCs plus PRF had efficient wound healing compared to the patients receiving PRF alone. Their results were consistent with other studies proposing that MSCs secrete high levels of VEGF and HGF, and maintain a higher ratio of transforming growth factor (TGF)-β3 to TGF-β1; this contributes to cell migration, proliferation, improvement of vascular angiogenesis, and matrix deposition [ 106 ]. They also promote wound reepithelization, modified collagen deposition, and reduce scar formation [ 106 , 107 ].…”
Section: Stem Cell Therapysupporting
confidence: 91%
See 1 more Smart Citation
“…Khalil et al reported that patients receiving AMSCs plus PRF had efficient wound healing compared to the patients receiving PRF alone. Their results were consistent with other studies proposing that MSCs secrete high levels of VEGF and HGF, and maintain a higher ratio of transforming growth factor (TGF)-β3 to TGF-β1; this contributes to cell migration, proliferation, improvement of vascular angiogenesis, and matrix deposition [ 106 ]. They also promote wound reepithelization, modified collagen deposition, and reduce scar formation [ 106 , 107 ].…”
Section: Stem Cell Therapysupporting
confidence: 91%
“…Furthermore, Khalil et al assessed the effectiveness of AMSCs embedded in autologous platelet-rich fibrin (PRF) on chronic DFU healing by comparing it to the treatment with PRF alone. They used this protocol as it has been assumed to be a cost-effective therapeutic approach, and better and faster than conventional chronic wound treatments [ 106 ]. Khalil et al reported that patients receiving AMSCs plus PRF had efficient wound healing compared to the patients receiving PRF alone.…”
Section: Stem Cell Therapymentioning
confidence: 99%
“…They followed this regimen since it is thought to be a more effective and efficient healing method than standard persistent wound care. 112 According to Khalil et al, 112 doing so does not give rise to any ethical concerns and the human placenta is less immunogenic than BM. Finally, a greater quantity of stem cells may be separated from the placenta than from BM.…”
Section: Adipose-derived Msc Therapy In Dfumentioning
confidence: 99%
“…In another study, the effects of implanting AMSCs in autologous platelet‐rich fibrin (PRF) were compared to the effects of using PRF alone to treat chronic DFU healing. They followed this regimen since it is thought to be a more effective and efficient healing method than standard persistent wound care 112 . According to Khalil et al, 112 individuals who received AMSCs in addition to PRF showed better wound healing than those who just received PRF.…”
Section: Stem Cell Therapymentioning
confidence: 99%
See 1 more Smart Citation